0.3-V, 357.4-nW Voltage-Mode First-Order Analog Filter Using a Multiple-Input VDDDA - Fabian Khateb; Montree Kumngern; Tomasz Kulej; Viera Stopjakova; Costas Psychalinos (My University, 2023)
In this paper, a new versatile first-order voltage-mode analog filter using a single multiple-input voltage differencing differential difference amplifier for extremely low-voltage supply and low-frequency applications is presented. Using multiple-input MOS transistor technique, the filter can realize the first-order transfer functions of non-inverting and inverting low-pass, high-pass, and all-pass filters in a single topology with high input and low output impedance. This is particularly useful for voltage-mode circuits. The filter's pole frequency can be controlled electronically. The filter was used to implement a new quadrature oscillator to confirm its advantages. The multiple-input was applied to bulk-driven differential pairs operating in weak inversion; therefore, the proposed circuit operated from a supply voltage of 0.3 V and consumed 357.4 nW. The circuit was designed in the Cadence program using 0.13 μm UMC CMOS technology. The performance and robustness of the design was validated by intensive simulations, including Monte Carlo and Process, Voltage and Temperature corner analyses.
Keywords: Analog and Mixed-Signal Circuit Design